Association Of Fgf21 Gene Polymorphism And Serum Fgf21 Levels In Type 2 Diabetes Mellitus Susceptibility - Kambali M, Shashank; Paluru, Rajesh; Anusha, R; E, Kayalvizhi; V, Ramnath (Journal of Neonatal Surgery, 2025)
Background:Fibroblast growth factor 21 is a key endocrine regulating protein factor involved in ontogenesis and metabolism, produced primarily in the liver, expressed in adipose tissue, skeletal muscle, pancreas, heart, and other organs. It increases insulin sensitivity, stimulates lipolysis, and suppresses lipogenesis in-turn affects glucose and lipid metabolism. The present study was aimed to screen for rs1800629 and rs1799964 polymorphisms in type 2 diabetic patients. Methods:A total of 100 samples comprising of 60 cases and 40 controls were enrolled. Patients were selected based on American Diabetes Association Criteria 2007, non-diabetic age matched healthy individuals were selected as controls. Following extraction of DNA, genotyping for rs838133 and rs499765 was performed by allele specific PCR. Appropriate statistical toolswere used to analyse the results. Results: The serum FGF21 levels was elevated in cases compared to controls (p<0.05). The distribution of genotypes for rs838133 varied significantly between the groups (p =0.02), however it was not for rs499765. The CC genotype of rs838133 demonstrated a four fold risk towards disease susceptibility while the A allele and C allele showed an OR of 0.44 and 2.25 respectively. Further categorization of cases into subgroups viz., cases who exercise and cases who do not exercise, did not significant results with respect to genotypes, however there was an allelic association. The A allele and allele C demonstrated an OR value of 0.33 and 3.0 respectively. For rs499765, the C allele and G allele revealed an OR value of 0.51 and 1.93 conferring its protective and predisposing role among cases who exercise and who do not exercise. Conclusion: FGF21 polymorphism appeared to be a potential molecular marker for diabetes risk in our population. This is the first report from South India; however, replicative studies considering other probable causative factors for T2DM risk are warranted.